IMPLEMENTATION OF MARKETING TOOLS TO INCREASE CUSTOMER LOYALTY - USTIK, Tetiana; KOLODNENKO, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the direction of customer loyalty management of the enterprise under the conditions of socially responsible marketing, substantiates the need to introduce marketing tools to increase customer loyalty, while developing measures taking into account the customer's life cycle. Attention is focused on the formation and strengthening of customer orientation of personnel on the basis of social and ethical marketing thanks to the developed author's management mechanism. Thanks to the evaluation of the quality of the corporate policy, recommendations were made to improve the quality of the staff's work with clients.Recognizing the importance of loyalty as an integral part of modern marketing is certainly an important step in modern theoretical and practical spheres. However, like any process that gains importance and has a certain impact on the economic result of the enterprise, it has clear results that need to be systematically managed. that is why the issue of consumer loyalty management is particularly relevant today.The lack of a global comprehensive approach to loyalty management, which is mainly explained by the fact that most of the materials on this issue are of a practical nature, that is, based on the experience of implemented programs and equated with the implementation of bonus and/or discount options, complicates the process of forming a correct understanding of the loyalty management process.Loyalty management is a very comprehensive process that has absolutely unique properties, manifestations, methods, risks, etc. The rapid development of information technologies and the intensification of competition on a global scale encourage the business sector to choose a development strategy based on building long-term relationships with customers. In the conditions when many products, services and services are offered on the market at almost the same prices, the formation of customer loyalty is one of the main arguments in the competition.
Keywords: loyalty; loyalty management strategy; customer orientation; customer life cycle; customer base; social and ethical marketing